Advertising As a Creative Industry : Regime of Paradoxes. - Derda, Izabela. (Routledge Research in the Creative and Cultural Industries Series, 2023)
At the crossroads of culture and commerce, the advertising industry is a regime of paradoxes. This book examines the place of advertising in today's creative industries, exploring the major challenges advertisers confront as they engage with other creative sectors.